A perspective of marginal microleakage in class II composite resin restorations using different types and techniques: an in-vitro study. - Alasbahi, Bassam (Journal of Oral Research; Vol 8 No 1, 2019)
The study aimed to introduce a perspective of the essential reason behind why marginal microleakage develops regardless of the composite type, the technique, or the bonding system applied, especially in gingival floor of class II cavities. Materials and Methods: Three types of composite resin materials (Charmfil TM , ParaFill TM , and ProMedica®) were used to evaluate microleakage of class II restorations using two restorative approaches. Twenty four newly extracted bicuspid teeth were divided into two main groups (n=12 each) according to the restoration technique (open or closed sandwich techniques). Teeth of each group were then divided into 3 groups (n= 4 each) according to the type of the composite resin used. The restorations were then subjected to a thermocycling process and then were immersed into methylene blue solution for 12 hours. Mesiodistal sectional cuts were made along the central grooves and assessed under stereomicroscope for marginal microleakage. The data were statistically analyzed with a p-value <0.05 considered significant. Results: There were no statistically significant differences in marginal microleakage between the three examined groups using both techniques ( p >0.05). Under the microscope, the marginal microleakage was more obvious at the cervical region than at the occlusal region. Conclusion: There was no effect of the composite type or the application technique used on the occurrence of marginal microleakage. The first portion of the material applied against the cavity floor is the primary factor involved in possibly minimizing marginal microleakage.
Keywords: Dental leakage; marginal microleakage; composite resins; sandwich technique; dental restoration.